Combined effects of acidification and warming on soil denitrification and microbial community - Peiyuan Xu; Peiyuan Xu; Mengke Gao; Mengke Gao; Yuchen Li; Yuchen Li; Jun Ye; Jianqiang Su; Jianqiang Su; Hu Li; Hu Li (Frontiers in Microbiology)
In light of the challenges posed by contemporary global warming and soil acidification, the respective effects of pH and temperature on soil microbiome and functions have been explored. However, the combined influence of acidification and warming on soil denitrification and active microbial communities are still unclear. Here, we conducted a microcosm experiment to investigate the influences of increasing temperature and acidification on active microbes such as bacteria and eukaryotic microbes. Denitrification rate in soil were detected using a C2H2 inhibition method. The results showed that the Shannon index of bacterial communities exhibited significant enhancement in response to warming and acidification, whereas their community patterns were predominantly shaped by pH. For the micro-eukaryotic community, temperature emerged as the main driver of variations in the α-diversity, with the MT group exhibiting significantly lower Shannon indices compared to LT and HT groups. Both pH and temperature exerted a combined effect on their community patterns. Additionally, pH was detected as a crucial factor influencing denitrification rates, with a significant negative correlation between pH and denitrification rate within the pH range of 4.32–7.46 across all temperatures in this study. Our findings highlighted the significant impacts of acidification on soil denitrification rates and active microbes under global warming, which provided an important scientific basis for agricultural production management and environmental protection in the context of global climate warming.